Picture book reading on the development of preschoolers in rural areas of China: Effects on language, inhibition, and theory of mind - Zheng, Yuanxia; Li, Danyang; Chen, Zhongqi; Liu, Guoxiong (Frontiers in Psychology, 2022)
Studies have shown that book reading intervention may scaffold children's language development. However, whether book reading interventions are equally effective for children's cognitive development in a Chinese rural school setting remains to be explored. We conducted a four-month book reading intervention to address these issues in rural Chinese areas. A total of three hundred twenty-one children aged between 2.56 and 6.47 years (M = 4.66 ages, SD = 0.80) were assigned to three groups as follows: (a) control group without donated picture books; (b) active reading control group with donated picture books; and (c) intervention group with a 4-month instructed picture book reading intervention. The findings indicate that the available books could produce significant positive changes in the development of receptive language (F(1,191) = 14.46, p < 0.01) and inhibitory control (F(1,190) = 7.64, p = 0.01) of rural children. However, a 4-month intervention was noneffective at boosting participants' performance on these tasks (F(1,203) = 0.07 2.73, p > 0.10). The results discussed the possible explanations, implications for behavioral intervention researchers, and suggestions for social service organizations or public institutions.